Measuring personality in Libyan Arabs: validating the big five aspect scale with 10 factors domain - Ali, Mohamed; Jahan, Alhadi M.; Abdelrahman, Rasha M. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Research has developed the Big-Five Aspect Scale (BFAS), supporting a five-domain model that includes 10 related aspects. In Arabic societies, there is currently a lack of validation evidence for a scale with these 10 aspects. Thus, this study develops and examines the psychometric properties of the short version of the BFAS (BFAS-SV) within Libyan Arab adults. The sample (N = 1136; 74.6% women, Mage = 25.30, SDage = 8.44) completed the original BFAS and the Arabic version of the International Personality Item Pool (IPIP) to assess the BFAS-SV’s convergent validity. Confirmatory Factor Analysis (CFA) was applied. The findings provide strong support for the presence of 10 distinct aspects within the Big Five personality domains. Additionally, a robust positive and negative correlation was found among the 10 BFAS-SV aspects, as well as between the BFAS-SV domains of Conscientiousness, Extraversion, Introversion, and Openness/Intellect and their corresponding dimensions in the IPIP, further confirming its concurrent and discriminant validity. Furthermore, the Cronbach’s alpha coefficients for the five domains and their respective 10 aspects ranged from 0.61 to 0.85, indicating good internal consistency. Significant gender differences were observed in the Neuroticism domain, particularly in its two aspects (Volatility and Withdrawal), as well as in the Openness/Intellect domain and the Politeness aspect, with women scoring higher in all cases. In conclusion, this study establishes the reliability, validity, and applicability of the Arabic BFAS among the Libyan Arab population. The insights gained into the personality traits and behaviors of Libyan Arab individuals provide valuable implications for personal development and professional success.